2012
DOI: 10.1021/ja307507a
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Cast Metal Oxide Thin Film Electrocatalysts for Oxygen Evolution

Abstract: Water oxidation is a critical step in water splitting to make hydrogen fuel. We report the solution synthesis, structural/compositional characterization, and oxygen evolution reaction (OER) electrocatalytic properties of ~2-3 nm thick films of NiO(x), CoO(x), Ni(y)Co(1-y)O(x), Ni(0.9)Fe(0.1)O(x), IrO(x), MnO(x), and FeO(x). The thin-film geometry enables the use of quartz crystal microgravimetry, voltammetry, and steady-state Tafel measurements to study the electrocatalytic activity and electrochemical propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

120
1,435
11
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,430 publications
(1,570 citation statements)
references
References 57 publications
120
1,435
11
4
Order By: Relevance
“…Therefore, most of the previously reported results related to BiVO 4 ‐based photoanodes13, 14, 16, 19, 47, 51, 52, 53 were measured in sulfite oxidation condition to show photo‐electrochemical properties of BiVO 4 ‐based electrodes independently of its poor water oxidation kinetics, as shown in Table S2 (Supporting Information). The photo‐electrochemical current densities of the BiVO 4 ‐based photoanodes4, 13, 14, 16, 17, 19, 20, 21, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 64, 65, 66, 67, 68, 69, 77 were plotted as a function of potential versus RHE. Thus, we measured PEC properties of BiVO 4 ‐based anodes under sulfite oxidation to figure out the effect of ligand engineering.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, most of the previously reported results related to BiVO 4 ‐based photoanodes13, 14, 16, 19, 47, 51, 52, 53 were measured in sulfite oxidation condition to show photo‐electrochemical properties of BiVO 4 ‐based electrodes independently of its poor water oxidation kinetics, as shown in Table S2 (Supporting Information). The photo‐electrochemical current densities of the BiVO 4 ‐based photoanodes4, 13, 14, 16, 17, 19, 20, 21, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 64, 65, 66, 67, 68, 69, 77 were plotted as a function of potential versus RHE. Thus, we measured PEC properties of BiVO 4 ‐based anodes under sulfite oxidation to figure out the effect of ligand engineering.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, under neutral condition, manganese oxide nanoparticles exhibited superior performance to previously reported transition metal–based catalysts 32, 33. Several researches show that Mn‐based oxides have superior catalytic activity at neutral pH and are highly active in water oxidation compared to low activity oxides, as shown in Table S1 (Supporting Information) 31, 32, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49. As compared to other OECs, Mn‐based oxides showed good catalytic properties (Tafel slope and overpotential) in the neutral pH condition for water oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…37 For electrodeposited catalyst electrodes, a literature method was used to electrodeposit IrO 2 . 38 An aqueous electrodeposition bath of 20 mM oxalic acid and 4 mM K 3 IrCl 6 was adjusted to pH 10 with Na 2 CO 3 and aged for >10 days.…”
Section: Catalyst Depositionmentioning
confidence: 99%
“…A recent report by the Boettcher group demonstrated that iron contamination is at the origin of its large OER activity 19. Subsequent studies have shown that iron serves multiple purposes for Ni(Fe)OOH catalysts:20 1) it adopts a different local environment with unusually short Fe−O bond distance as shown by operando X‐ray absorption spectroscopy (XAS);21 2) it modifies the redox activity of nickel;17 and 3) it improves the electronic conductivity of the film 22.…”
mentioning
confidence: 99%